2018
DOI: 10.20533/ijcdse.2042.6364.2018.0469
|View full text |Cite
|
Sign up to set email alerts
|

“Schools: Future Labs” – Combining the Teaching of Sciences and Foreign Language

Abstract: The Erasmus+ project Schools: Future Labs (SFL) was funded under the Key Action 2: Cooperation for innovation and exchange of good practices-Strategic partnerships in the field of education, training and youth of the Erasmus+ program. Its main objective was to increase the employability of young people, by getting them interested in STEM (Science, Technology, Engineering, and Mathematics) subjects and in the habit of using a foreign language. To reach its objective, Schools: Future Labs developed and tested a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Gikopoulou et al (2018) evaluated a Physics CLIL project through L2 German as part of a three-year Erasmus+ project. The authors observed an increase in students' motivation and interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gikopoulou et al (2018) evaluated a Physics CLIL project through L2 German as part of a three-year Erasmus+ project. The authors observed an increase in students' motivation and interest.…”
mentioning
confidence: 99%
“…Students improved their attitudes, skills, cooperation, and performance in both L2 German and Science, Technology, Engineering and Mathematics (STEM) content. Teachers reported time constraints and challenging lesson planning, despite being satisfied with the methodology and acquiring additional skills that strengthened their professional profile Gikopoulou et al (2018). also concluded with a positive evaluation of their CLIL project.…”
mentioning
confidence: 99%